Collectors, Crusaders, Carers, and Tourist Networks in Possessing Mandate Palestine. (1st November 2013) - Butler, Beverley
Abstract : This paper is taken from a wider body of research that focuses upon selected institutions, groups, and individuals — the collectors, crusaders, and carers of my title — that are bound up in the historical and contemporary (cultural-political) project of 'possessing Palestine' (Butler, forthcoming). My research explores the ways in which the desire to 'possess Palestine' — whether as a pilgrim, tourist, crusader, archaeologist, missionary, and/or colonizer — moves from a metaphorical to a literalizing force of ownership. My specific focus in this paper explores this dynamic vis-à-vis the part played by Freemasons and Freemasonry, with a particular emphasis placed upon the creation of the first permanent English lodges within the networks of empire and tourism during the British Mandate period in Palestine. As such my purpose is to engage with an oft-neglected yet, as I argue, highly potent phenomenon at work in the Mandate context: Masonic networks that span popular and elite, and social and professional worlds, that are inextricably linked by exploration and archaeological endeavour, to formal Masonic missions and a specific tradition of 'Masonic tourism'. My purpose is therefore twofold: firstly to explore the significances located in the establishment of such institutional and personal-social networks and how these relate to the circulation of a constant stream of persons, things, and ideas between and across Britain and Palestine. Secondly, I am interested in how the project of 'possessing Palestine' and as I wish to argue — being 'possessed by' Palestine — is bound up in the structuring of 'imaginative geographies' (Said, 1994) that strategically co-opt both the empirical scientism of archaeology with the more esoteric dimensions of Palestine as 'imaginative entity', so that these twin lenses operate effectively together to be pressed into the service of literalizing the British claim to Palestine, Jerusalem, and to Masonic heritage. I am thus interested in the importance given to sustaining — and/or in some instances to disrupting and reshaping — these flows and to see them rather than as fixed points, as a complex nexus of movements that draw on the appeal that Jerusalem, Palestine and the 'Holy Land' exerts across sacred and profane worlds.